1996
DOI: 10.1002/stem.140225
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously Produced Interleukin 6 is an Accessory Cytokine for Dendritic Cell Hematopoiesis

Abstract: Abstract. The aim of this study was to investigate the role of interleukin 6 (IL-6) in normal dendritic cell (DC) hematopoiesis. We used an enzyme-linked immunosorbent assay to quantitate IL-6 levels in CD34 + progenitor cell cultures favoring monocyte (mono) development versus those supporting mono-DC growth, and studied the neutralizing effects of αIL-6 antibody on DC hematopoiesis. IL-6 levels in mono cultures (GM-CSF alone) were detected by day 4 and remained constant (~100 pg/ml) for 18 days. In mono-DC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Our data demonstrating that IL-6 inhibits BMDC generation are consistent with several previous findings that IL-6 prevents monocytes from differentiating into DC (11,14). However, Santiago-Schwarz et al (16) showed that when CD34 ϩ progenitor cells were cultured with GM-CSF, TNF-␣, and stem cell factor, the yield of DC was increased in cultures with higher supernatant IL-6 levels and reduced by the addition of an anti-IL-6 Ab. In contrast to our findings of increased BMDC generation from IL-6 Ϫ/Ϫ bone marrow culture in GM-CSF, Brasel et al (15) demonstrated that IL-6 Ϫ/Ϫ bone marrow cultured solely in Flt-3 ligand produced much fewer BMDC than WT bone marrow.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data demonstrating that IL-6 inhibits BMDC generation are consistent with several previous findings that IL-6 prevents monocytes from differentiating into DC (11,14). However, Santiago-Schwarz et al (16) showed that when CD34 ϩ progenitor cells were cultured with GM-CSF, TNF-␣, and stem cell factor, the yield of DC was increased in cultures with higher supernatant IL-6 levels and reduced by the addition of an anti-IL-6 Ab. In contrast to our findings of increased BMDC generation from IL-6 Ϫ/Ϫ bone marrow culture in GM-CSF, Brasel et al (15) demonstrated that IL-6 Ϫ/Ϫ bone marrow cultured solely in Flt-3 ligand produced much fewer BMDC than WT bone marrow.…”
Section: Discussionsupporting
confidence: 93%
“…Brasel et al (15) established that blocking IL-6 function reduced the number of DC generated in Flt-3 ligand-supplemented murine wild-type (WT) bone marrow cultures. In another report, higher IL-6 levels correlated with greater DC yield in cultures of CD34 ϩ cells (16). Although DC are known to produce IL-6, data regarding the contribution of IL-6 secretion to DC function are sparse.…”
mentioning
confidence: 97%
“…Even following stimulation with LPS, TNF-α, and Der p, the percentages of CD11c + BMDCs from IL-6 KO mice did not increase as compared to those from WT mice, implying that IL-6 can promote DC generation. In a previous study, IL-6 levels were also positively correlated with DC yield in CD34 + progenitor cell culture [31]. Our results appear to contrast the report of Bleier et al [32], which shows that IL-6 KO BMs generate more CD11c + BMDCs than WT BMs.…”
Section: Discussioncontrasting
confidence: 88%
“…IL-6 is a key cytokine in DC development [32]. IL-6 is also an important inflammatory response mediator in DCs [33], [34].…”
Section: Resultsmentioning
confidence: 99%
“…IFN-γ and IL-12 can be produced by DCs, enhance the antigen presenting capabilities of DCs, and support initiation and modulation of adaptive immune responses [50]. Higher IL-6 levels were correlated with DC content and development [32]. In contrast to S2308, RB51 was able to trigger a potent secretion of TNF-α, IL-12/IL23p40, IFN-γ, and IL-6 from WT BMDCs.…”
Section: Discussionmentioning
confidence: 99%